Pengendalian Kualitas Produk Pipa Carbon Seamless Menggunakan Peta Kendali Dan Kapabilitas Proses - Hidayat, Dian Friana; Sutaarga, Ossa; Hardono, Joko (Journal Industrial Manufacturing, 2023)
The company's efforts to continuously improve quality in monitoring and measuring product characteristics to check that product requirements have been met so that the product realization process is in line with planned arrangements. As for PT. CTA always maintains process capability based on predetermined specifications for seamless carbon pipe products, including indicators of pipe roundness and thickness. The method used in this study is the X-bar and R control chart and process capability used to measure and evaluate whether the process is in statistically controlled quality or not and measure the performance relationship between the actual process and predetermined specification limits so that it can be carried out maintenance plan. The results of this study are first, 2 iterations of the control chart because previously some data were obtained that were not within the upper or lower control limits. Second, the results of measuring process capability are the Cpk value of 0.563 and the CP value of 0.587 (Cp <1) which means that the process capability to meet the specified specifications is low. Third, measurement of the total non-conformance level of 988,100 ppm or 988,100 units that do not comply with the desired specifications in one million products produced. Keyword: X-Bar and R Control Chart, Capability Process, Statistical Quality Control, Nonconformance